Much love, little esteem and (almost) no recognition: the work of teachers under the perspective of axel honneth - Mariana Jacinto Figueiredo (Instituto Federal de São Paulo, 2018)
The paper proposes a comparative analysis about the divergent points of Career Plans of high school teachers and higher education teachers in the state of Paraná, under the bias of the Theory of Recognition addressed by Axel Honneth. The author affirms that for recognition there is a need for the process to go through the sphere of love, law and esteem. In this sense, the paper makes a brief initial approach to how the teacher figure transits these spheres in different ways. Finally, we make an analysis of the recognition of both positions of teachers, using as empirical object the career plan of both.